ANALISIS KINERJA STRUKTUR ATAS BANGUNAN RTMC POLDA MALUKU MENGGUNAKAN METODE STATIC NON-LINEAR - Markus, Leviona; Frans , Pieter Lourens; Hutubessy , Vector R. R (Journal Agregate, 2024)
Ambon City is one of the cities in Moluccas which is also one of the earthquake-prone areas which is classified in earthquake zone 5. Several structural elements of the Moluccas Police RTMC building in the realization of fieldwork were not by the planning results. The research aimed to produce displacement values ​​and obtain the performance of the structural of the Maluku Regional Police RTMC building against earthquake forces after being analyzed by non-linear static analysis with the help of SAP2000 v.22. Research shows that the movement between floors is still safe because it does not exceed the drift limit of 30 mm where the largest displacement in the x direction occurs due to a dynamic earthquake (DX) on the roof floor, about 10.443 mm, and the largest displacement in the y direction occurs due to loads due to dynamic earthquakes (DY) on the roof floor about 28.514 mm. The performance evaluation for the XZ direction is still in a safe condition because the plastic hinge distribution scheme does not show structural members that pass the immediate occupancy (IO), and happen strong column weak beams occur if the loading step is enlarged, this is indicated by the absence of column elements that achieve IO performance. The performance of the YZ direction is still in a safe condition because the plastic hinge distribution scheme does not show that the structural members pass the IO performance and happen strong column weak beams occur when the loading step is increased.